Immunomodulatory effect of stingless bee honey on wound healing mechanism in LPS-activated RAW 264.7 cells - Ab. Hadi, Hazrina; Kasmuri, Abdul Razak; Abdul Jalil, Mohd Azri (2019)
INTRODUCTION: In wound healing mechanism, macrophages are involved as part of the cleaning of the microenvironment and thus promote the healing process. Several researches indicated that the depletion of macrophages could delay the re-epithelization and hinder the vascular formation due to the upregulation of inflammatory mediators and downregulation of growth factors. OBJECTIVES: The objectives of this study were to elucidate the effect of stingless bee honey on the wound healing mechanism by using LPS-activated RAW 264.7 macrophage model. MATERIALS AND METHODS: The inflammatory effect of murine macrophage cell line RAW 264.7 was stimulated by incubation with lipopolysaccharide (LPS). The macrophages were group into three different concentration of honey’s treatment, a blank and a control group. A competitive enzyme-linked immunosorbent assay (ELISA) kit was used to quantify the concentration of PGE2 while sandwich ELISA kit was used to measure the concentration of IL-1b, IL-6, and TNF-a. RESULTS: In acute inflammation, pro-inflammatory cytokines need to be upregulated to promote the healing processes. However, prolonged production of these pro-inflammatory cytokines can overdue the inflammatory process leads to chronic inflammation and hinder the healing process. Honey plays a unique role on these inflammation phase, which can act as a pro-inflammatory agent at one point and another point, worked as anti-inflammation agent to promote the wound healing, a term proposed by a few researchers as an immunomodulator. CONCLUSIONS: In conclusion, stingless bee honey has the immunomodulator properties to balance the production of pro-inflammatory cytokines when the level of cytokines is reduced or upsurge.